2018
DOI: 10.1080/09513590.2018.1459549
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ovarian reserve and ovarian blood flow in patients with polycystic ovary syndrome following laparoscopic ovarian drilling

Abstract: This prospective cohort study was conducted on 80 patients with clomiphene citrate (CC)-resistant polycystic ovary syndrome undergoing laparoscopic ovarian drilling (LOD). Pre- and post-LOD ovarian reserve parameters (anti-Mullerian hormone: AMH, ovarian volume: OV, and antral follicle count: AFC) and ovarian stromal blood flow indices (Vascularization index: VI, flow index: FI, and vascularization flow index: VFI) were measured to explore the effect of LOD and to find out the correlation between serum AMH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Similarly, the degree of testosterone decreased from small follicles to dominant follicles of poor responders was significantly dramatic than those in the other two groups. Correspondingly, results obtained from dynamic changes of serum hormone profile showed that both AMH and testosterone levels decreased immediately after TVOD in poor responders (we consider that the reduced AFC and the decreased levels of the two hormones in these small follicles are the main reasons [41,42]) (Fig. 2.).…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, the degree of testosterone decreased from small follicles to dominant follicles of poor responders was significantly dramatic than those in the other two groups. Correspondingly, results obtained from dynamic changes of serum hormone profile showed that both AMH and testosterone levels decreased immediately after TVOD in poor responders (we consider that the reduced AFC and the decreased levels of the two hormones in these small follicles are the main reasons [41,42]) (Fig. 2.).…”
Section: Discussionmentioning
confidence: 58%
“…We found fewer studies to report the correlations between AMH and Doppler ultrasonography measures. Elmashad et al ( 17 ) and Kamal et al ( 33 ) found significant positive correlations between AMH levels and VI and FI in women with PCOS. Several studies of infertile women have reported that serum AMH levels correlate positively with AFC whereas FSH levels correlate negatively with AFC ( 44 - 46 ).…”
Section: Discussionmentioning
confidence: 96%
“…Another problem associated with PCOS is the inability to conceive; 65.2% of patients with PCOS report primary infertility, and 34.8% reported secondary infertility [ 9 , 15 , 18 , 25 , 28 , 40 ]. The average amount of punctures done during the procedure was 12.58 in each ovary across all studies (range: 3-120) [ 7 - 10 , 13 - 17 , 19 , 20 , 22 , 23 , 27 - 30 , 36 , 41 , 42 ].…”
Section: Reviewmentioning
confidence: 99%